Pengaruh Model Pembelajaran Kooperatif Tipe Index Card Match Terhadap Hasil Belajar Matematika Siswa Kelas V UPTD SD Negeri 122345 Pematangsiantar - Agustina Sidabukke; Theresia Monica Siahaan; Emelda Thesalonika (Lembag, 2024)
The aim of this research is to determine the effect of the index card match type cooperative model on the Mathematics learning outcomes of class V UPTD students at SD Negeri 122345 Pematangsiantar. This research is a pre-experimental research using a one group pretest-posttest design, the sample of this research is 23 people. The data collection technique is a test. By carrying out the pretest, they got an average result of 55.87, then they were given treatment after being given treatment using the cooperative index card match type model, so they got a posttest score with an average value of 85.22. With the scores obtained, the posttest scores have a higher average than the pretest. After carrying out the posttest, the researcher carried out a normality test. From the data test, the results were that the data was normally distributed. Based on the results of data analysis using hypothesis testing. The results of the t test obtained t = 16,960 with a significance level of 0.000. because the significant probability is much smaller than 0.05, namely 0.000 and tcount = 16,960 > ttable = 1,717, then HO is rejected and Ha is accepted. This shows that it means that there is an influence of the index card match type cooperative learning model on the Mathematics learning outcomes of fifth grade students at UPTD Elementary School, State Elementary School 122345 Pematangsiantar for the 2024/2025 academic year.